Seasonal migration and early childhood development - Karen Macours; Renos Vakis (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper provides unique evidence of the positive consequences of seasonal migration for investments in early childhood development. We analyse migration in a poor shockprone border region in rural Nicaragua where it offers one of the main household income diversification and risk coping strategies. IV estimates show, somewhat surprisingly, that mother's migration has a positive effect on early cognitive development. We attribute these findings to changes in income and to the intrahousehold empowerment gains resulting from mother's migration, which offset potential negative ECD effects from temporary lack of parenting. This paper, hence, illustrates how increased opportunities in seasonal migration due to higher South-South mobility might positively affect early childhood development and as such long term poverty reduction.
Keywords: O15; J61; 330; Nicaragua; migration; income; households; Saisonarbeitskräfte; Regionale Arbeitsmobilität; Kinderbetreuung; Nicaragua